2008
DOI: 10.1111/j.1524-4725.2007.34117.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applicability of in vivo Reflectance Confocal Microscopy for the Diagnosis of Actinic Keratoses

Abstract: In summary, RCM may be a promising technology for the noninvasive detection of AK and as adjunct tool to clinical diagnosis and monitoring. However, the preliminary nature of this study warrants further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 30 publications
6
90
0
5
Order By: Relevance
“…Another patient (patient 2) showed clearance on clinical examination but persistence of AK features (atypia of the stratum granulosum and spinosum) and inflammation on RCM examination. Overall, the stratum corneum showed a more homogeneous appearance and increased cohesiveness of corneocytes comparable to findings observed in normal, unaffected skin sites [25,26,27]. RCM images obtained at the level of the stratum granulosum and spinosum showed a more regular appearance of keratinocytes, with polygonal cells arranged in a typical honeycomb pattern (9/11).…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Another patient (patient 2) showed clearance on clinical examination but persistence of AK features (atypia of the stratum granulosum and spinosum) and inflammation on RCM examination. Overall, the stratum corneum showed a more homogeneous appearance and increased cohesiveness of corneocytes comparable to findings observed in normal, unaffected skin sites [25,26,27]. RCM images obtained at the level of the stratum granulosum and spinosum showed a more regular appearance of keratinocytes, with polygonal cells arranged in a typical honeycomb pattern (9/11).…”
Section: Resultsmentioning
confidence: 54%
“…In an attempt to increase diagnostic accuracy with noninvasive imaging technologies, a number of adjunct diagnostic devices have been evaluated for their clinical applicability. Among others, recent studies reported high sensitivity and specificity rates for diagnosis of AK by RCM in vivo [26,27]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations